Formation of key competencies of the organization: the concept «from points to space» - S. B. Moiseev (Путеводитель предпринимателя)
The urgency of the task of using key competencies in the formation of the competitive potential of an industrial enterprise has been substantiated. The role and place of key competencies in the implementation of the concept «from points to space» has been determined. The results of a study on the identification of key competencies of a large Russian enterprise engaged in the production of high–voltage bushings are presented.